Potterian economics - Daniel C. Levy; Avichai Snir (Bar-Ilan University, Department of Economics, 2017)
Recent studies in psychology and neuroscience find that fictional works exert strong influence on readers and shape their opinions and worldviews. We study the Potterian economy, which we compare to economic models, to assess how Harry Potter books affect economic literacy. We find that some principles of Potterian economics are consistent with economists' models. Many others, however, are distorted and contain numerous inaccuracies, which contradict professional economists' views and insights, and contribute to the general public's biases, ignorance, and lack of understanding of economics.
Keywords: A13; A14; D72; D73; H00; H11; I20; P16; P48; P51; Z11; Z13; 330; Economic and Financial Literacy; Political Economy; Public Choice; Rent Seeking; Folk Economics; Harry Potter; Social Organization of Economic Activity; Literature; Fiction; Potterian Economy; Potterian Economics; Popular Opinion